Early Antimicrobial Therapy for Sepsis: Does Each Hour Really Count? - Guery, Benoit; Calandra, Thierry (Seminars in Respiratory and Critical Care Medicine, 2019)
For the last decades, the timing of antimicrobial therapy has remained a hotly debated topic in sepsis as well as other infectious diseases like community-acquired pneumonia (CAP) or bacterial meningitis (CABM). In CAP, a relationship between the time to antibiotic administration and mortality was found only in the largest cohort, but all these studies were retrospective and of low quality. In CABM, the level of evidence remains also limited, but there is now a good body of evidence linking the delay to antibiotic administration to unfavorable outcome. The European guidelines strongly suggest that time period should not exceed 1 hour. Finally, in sepsis, if the 1-hour cut-off remains debatable for sepsis patients, early administration (within 3 hours) is recommended in sepsis and sepsis shock as suggested by the surviving sepsis campaign recommendations. To conclude, all these data are in favor of a potential link between the time to antibiotic administration and survival, but we still miss randomized controlled studies to give a definite answer.
Keywords: antibiotic timing; sepsis; septic shock; meningitis; community-acquired pneumonia